Gravity Load Collapse Behavior of Nonengineered Reinforced Concrete Columns - Chichaya Boonmee; Kittipoom Rodsin; Krissachai Sriboonma (Advances in Civil Engineering)
This paper aims at investigating gravity load collapse behavior of extremely poor quality reinforced concrete columns under cyclic loading. Such columns were usually constructed by local people and may not be designed to meet any of the standards. It was found that their concrete strength may be as low as 5 MPa and the amount of longitudinal reinforcement may be lower than 1%. This type of column is deliberately defined as “nonengineered reinforced concrete column,” or NRCC. During earthquake, the gravity load collapse of the NRCC columns caused a large number of death tolls around the world. In this study, four columns as representative of existing NRCC were tested under cyclic loading. The compressive strength of concrete in order of 5 MPa was used to be representative of columns with poor quality concrete. Two axial load levels of 6 and 18 tons were used to study the influence of axial load level on maximum drift at gravity load collapse. To investigate the effect of bar types on drift capacity, 9 mm round bars were used in two specimens and 12 mm deformed bars were used for the rest of the specimens. The maximum drift before gravity load collapse was very dependent on the axial load level. The maximum drift of the specimens subjected to high axial load (18 tons) was extremely low at approximately 1.75% drifts. The use of deformed bars (associated with larger amount of longitudinal reinforcement) caused the damage to severely dissipate all over the height of the columns. Such damage caused columns to collapse at a lower drift compared to those using round bars. Finally, the plastic hinge model was used to predict the maximum drift of the low strength columns. It was found that the model overly underestimates the drift at gravity load collapse.